Morphological and Molecular Characterization of Heterodera schachtii and the Newly Recorded Cyst Nematode, H. trifolii Associated with Chinese Cabbage in Korea - Abraham Okki Mwamula; Hyoung-Rai Ko; Youngjoon Kim; Young Ho Kim; Jae-Kook Lee; Dong Woon Lee (The Plant Pathology Journal, 2019)
Two-component systems (TCSs) are critical to the pathogenesis of Xanthomonas oryzae pv. oryzae (Xoo). We mutated 55 of 62 genes annotated as responsive regulators (RRs) of TCSs in the genome of Xoo strain PXO99A and identified 9 genes involved in Xoo virulence. Four (rpfG, hrpG, stoS, and detR) of the 9 genes were previously reported as key regulators of Xoo virulence and the other 5 have not been characterized. Lesion lengths on rice leaves inoculated with the mutants were shorter than those of the wild type and were significantly restored with gene complementation. The population density of the 5 mutants in planta was smaller than that of PXO99A at 14 days after inoculation, but the growth curves of the mutants in rich medium were similar to those of the wild type. These newly reported RR genes will facilitate studies on the function of TCSs and of the integrated regulation of TCSs for Xoo pathogenesis.